Integration Of Al-Quran and Hadith Values ​​in Developing Learning Curriculum - Maesaroh Lubis; Farida Isroani (Institut Attanwir Bojonegoro, 2025)
This research aims to analyze the content of the verses of the Qur'an and hadith related to learning strategies, with a descriptive qualitative approach using library research methods. The focus of this research is to explore how the principles of Islamic teachings contained in the Qur'an and hadith can be applied in effective learning strategies in modern education. in designing holistic learning strategies and educating students not only in aspects of knowledge, but also in the formation of morals and ethics. The purpose of this research is to identify and analyze the verses of the Qur'an and Hadith related to learning strategies, and to explore how their implementation can improve the quality of education. In an effort to achieve this goal, this study will examine various religious texts that explicitly mention the principles of education, learning, and teaching in the context of Islam. By analyzing relevant verses and Hadith, it is hoped that a strong theoretical basis can be found that supports the development of effective learning methods. Furthermore, this study will also consider the social and cultural context in the implementation of these strategies, so that it can provide contextual and applicable recommendations for educators. Through a deep understanding of Islamic teachings and their applications